The New Area-Wide Model of the euro area: a micro-founded open-economy model for forecasting and policy analysis - Kai Christoffel; Günter Coenen; Anders Warne (European Central Bank (ECB), 2008)
In this paper, we outline a version of the New Area-Wide Model (NAWM) of the euro area designed for use in the (Broad) Macroeconomic Projection Exercises regularly undertaken by ECB/Eurosystem staff. We present estimation results for the NAWM that are obtained by employing Bayesian inference methods and document the properties of the estimated model by reporting its impulse-response functions and forecast-error-variance decompositions, by inspecting the model-based sample moments, and by examining the model's forecasting performance relative to a number of benchmarks, including a Bayesian VAR. We finally consider several applications to illustrate the potential contributions the NAWM can make to forecasting and policy analysis.
Keywords: C11; C32; E32; E37; 330; Bayesian inference; DSGE modelling; euro area; forecasting; open-economy macroeconomics; policy analysis; Makroökonometrie; Offene Volkswirtschaft; Mikrofundierung; Wirtschaftsprognose; Eurozone; Dynamisches Gleichgewicht; EU-Staaten